2022
DOI: 10.3389/fnins.2022.887478
|View full text |Cite
|
Sign up to set email alerts
|

Modifying PCDH19 levels affects cortical interneuron migration

Abstract: PCDH19 is a transmembrane protein and member of the protocadherin family. It is encoded by the X-chromosome and more than 200 mutations have been linked to the neurodevelopmental PCDH-clustering epilepsy (PCDH19-CE) syndrome. A disturbed cell-cell contact that arises when random X-inactivation creates mosaic absence of PCDH19 has been proposed to cause the syndrome. Several studies have shown roles for PCDH19 in neuronal proliferation, migration, and synapse function, yet most of them have focused on cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…However, residual clustering and limited migration away from the injection site have also been reported 29,33 . Since factors transiently expressed in developing brain e.g., clustered gamma-protocadherins 34,35 or CCCTC-binding factor 36 can influence migration and integration of MGE progenitor cells, we here investigated integration following transplantation into recipient mice at different developmental ages. Because factors 10 expressed in local microcircuits e.g., vesicular GABA transporters 32 or MTG8 37 can also influence integration of these progenitors, we compared transplantations into cortex and hippocampus (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, residual clustering and limited migration away from the injection site have also been reported 29,33 . Since factors transiently expressed in developing brain e.g., clustered gamma-protocadherins 34,35 or CCCTC-binding factor 36 can influence migration and integration of MGE progenitor cells, we here investigated integration following transplantation into recipient mice at different developmental ages. Because factors 10 expressed in local microcircuits e.g., vesicular GABA transporters 32 or MTG8 37 can also influence integration of these progenitors, we compared transplantations into cortex and hippocampus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second, precursors for MGE-derived interneuron subtypes could be subject to programmed cell death during neurodevelopment. This process is regulated by region-specific expression of environmental factors like pcdh 34,35,49 , c-Maf 50 or PTEN 44 which facilitate postnatal survival and/or maturation of PV+ and SST+ interneurons. Given that these are developmentally regulated expression patterns it is not surprising that juvenile and adult brains were less receptive to integration of transplanted MGE progenitors than mouse pups or the differences in PV/SST ratios seen here (Fig 4).…”
Section: Discussionmentioning
confidence: 99%
“…This targeted loss specifically in interneurons might have compromised integration into the Pcdh10- positive BLC. Previous studies have revealed a strong association between several non-clustered protocadherins and sorting defects observed both in vitro and in the developing brain, including the formation of specific aggregates due to differential δ2-protocadherin expression in vitro (81), sorting anomalies and reduced interneuron migration in the cortex of Pcdh19 mosaic females (81,83) and the mislocalization of Gad1- expressing cells in the thalamus of Pcdh10b knockdown zebrafish (97). These findings collectively suggest that loss of protocadherin expression in adjacent cells might affect their positioning and circuit integration.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, genetic variants in PCDH19 have been linked to a rare newly individualized syndrome: epilepsy in females with mental retardation (EFMR), also known as early infantile epileptic encephalopathy (EIEE9) or PCDH-19 clustering epilepsy (OMIM #300088), and in fact comes second in the list of genes associated with this disease [ 31 , 32 ]. This sex-limited disease is characterized by the early onset of seizures, usually with varying degrees of intellectual disability [ 33 ] and other neurobehavioral features [ 34 ].…”
Section: Discussionmentioning
confidence: 99%